Trend of Increasing Health Budget in Indonesia's State Budget During COVID-19 Pandemic - Victor Asido Elyakim P; Bagas Adi Nata; M.Alfathan Haris; Mirza Afif Pradivta; Muhammad Rizky Ramadhan (Yayasan Literasi Sains Indonesia, 2025)
This research aims to analyze trends and allocation of Indonesia's health budget during 2010-2022 period based on state budget realization and projection data. The analysis was conducted on three main components of the health budget, namely central government expenditure through Ministries/Institutions, transfers to regions and village funds, and health financing. Based on the analysis results, the health budget experienced significant increase from IDR 29.89 trillion in 2010 to IDR 255.39 trillion in 2022, with the ratio to total state expenditure increasing from 2.9% to 9.4%. The Ministry of Health became the largest allocation recipient in the central government expenditure category, while the regional transfer component showed consistent growth through Special Allocation Fund (DAK) for Health and Operational Health Assistance (BOK). Drastic increases in health budget occurred during 2020-2022 period, caused by COVID-19 pandemic response through various special programs such as health budget reserves, earmarked General Allocation Fund (DAU), and village funds for COVID-19 response. The results of this research provide a comprehensive overview of the Indonesian government's commitment in the health sector and can serve as a basis for evaluating the effectiveness of health budget allocation in the future.